PEMANFAATAN LIMBAH KULIT NANAS UNTUK PEMBUATAN TEPACHE SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DESA KUALU NENAS: UTILIZATION OF PINEAPPLE PEEL WASTE FOR TEPACHE PRODUCTION AS AN EMPOWERMENT EFFORT FOR THE COMMUNITY OF KUALU NENAS VILLAGE - Siti Nazhifah; Maria Erna; Susilawati; Putri Adita Wulandari; Wulandari (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This community service activity was conducted in Kualu Nenas Village, Tambang Subdistrict, Kampar Regency, to increase residents' knowledge and skills in processing pineapple peel waste into Tepache fermented drink. The activity method consisted of two main stages, namely socialization and Tepache making training, which 30 participants attended. The socialization focused on increasing understanding of the benefits and economic potential of the product. At the same time, the training was conducted directly through Tepache production practices with the assistance of the community service team. Evaluation was carried out through participant satisfaction questionnaires and taste preference tests. The questionnaire results showed that 100% of participants stated that this activity broadened their knowledge, 95% understood the steps for making Tepache well, and 90% stated that they were interested in trying to make Tepache independently. Taste preference tests by 20 panelists showed that 83% of panelists liked the Tepache product with its sweet and sour taste and refreshing pineapple aroma. This activity effectively empowered the community and encouraged the productive, economically valuable, and environmentally friendly management of pineapple peel waste